Walruses are potentially exposed to paralytic shellfish toxin concentrations that impact their health during Alexandrium blooms in the Alaskan Arctic - Patrick Charapata; Evangeline Fachon; Donald M. Anderson; Gay Sheffield; Emily K. Bowers; Robert S. Pickart; Peigen Lin; Kathi A. Lefebvre (Harmful Algae, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Saxitoxin Linked to Deaths of Northern Fur Seals in the Southeast Bering Sea - Kathi A. Lefebvre; Chelsea M. Campbell; Lauren M. Divine; Paul Melovidov; Hanna Hellen; Kathy Burek Huntington; Emily K. Bowers; Natalie Rouse; Evangeline Fachon; Thomas J. Farrugia; Robert S. Pickart; Peigen Lin; et al. (Marine Mammal Science, 2025)
In August 2024, a northern fur seal mortality event was observed on St. Paul Island, AK in the southeast (SE) Bering Sea. Ten seals in good body condition were found dead along with large accumulations of dead fish on Benson Beach located on St. Paul Island. Full necropsies of the five available adult seals, one pup, and several fish did not reveal any overt causes of death. Testing of tissues for the algal neurotoxins domoic acid (DA) and saxitoxin (STX) confirmed the presence of STX in multiple tissues and physiological exposure in all five adult NFS and the two fish available for testing. DA was not detected in any samples. Complimentary samples of the SE Bering Sea ecosystem during the same time frame and location as the die off revealed bloom densities of Alexandrium catenella (the dinoflagellate that produces STX), large A. catenella cyst beds, and high prevalences of STX in fish (100%, n = 22), zooplankton (93%, n = 28), clams (100%, n = 10) and worms (93% n = 15) in the foraging area of NFS. High STX concentrations were observed in fish, clams, worms, and NFS urine, providing compelling evidence for a STX poisoning event.

Upper-layer circulation at the mouth of Amundsen Gulf, Arctic Ocean - Peigen Lin; Robert S. Pickart; Maria Pisareva; Bill Williams (Progress in Oceanography, 2025)

The Pacific water flow branches in the eastern Chukchi Sea - Robert S. Pickart; Peigen Lin; Frank Bahr; Leah T. McRaven; Jie Huang; Astrid Pacini; Kevin R. Arrigo; Carin J. Ashjian; Catherine Berchok; Mark F. Baumgartner; Kyoung-Ho Cho; Lee W. Cooper; et al. (Progress in Oceanography, 2023)

Formation and circulation of newly ventilated winter water in the western Beaufort Sea - Peigen Lin; Robert S. Pickart; Thomas J. Weingartner; Harper L. Simmons; Motoyo Itoh; Takashi Kikuchi (Progress in Oceanography, 2023)

Coastal upwelling enhances abundance of a symbiotic diazotroph (UCYN-A) and its haptophyte host in the Arctic Ocean - Corday R. Selden; Sveinn V. Einarsson; Kate E. Lowry; Katherine E. Crider; Robert S. Pickart; Peigen Lin; Carin J. Ashjian; P. Dreux Chappell (Frontiers in Marine Science, 2022)
The apparently obligate symbiosis between the diazotroph Candidatus Atelocyanobacterium thalassa (UCYN-A) and its haptophyte host, Braarudosphaera bigelowii , has recently been found to fix dinitrogen (N 2 ) in polar waters at rates (per cell) comparable to those observed in the tropical/subtropical oligotrophic ocean basins. This study presents the novel observation that this symbiosis increased in abundance during a wind-driven upwelling event along the Alaskan Beaufort shelfbreak. As upwelling relaxed, the relative abundance of B. bigelowii among eukaryotic phytoplankton increased most significantly in waters over the upper slope. As the host’s nitrogen demands are believed to be supplied primarily by UCYN-A, this response suggests that upwelling may enhance N 2 fixation as displaced coastal waters are advected offshore, potentially extending the duration of upwelling-induced phytoplankton blooms. Given that such events are projected to increase in intensity and number with ocean warming, upwelling-driven N 2 fixation as a feedback on climate merits investigation.

Large quantities of small microplastics permeate the surface ocean to abyssal depths in the South Atlantic Gyre - Shiye Zhao; Erik R. Zettler; Ryan P. Bos; Peigen Lin; Linda A. Amaral‐Zettler; Tracy J. Mincer (Global Change Biology, 2022)
Hundreds of studies have surveyed plastic debris in surface ocean gyre and convergence zones, however, comprehensive microplastics (MPs, ≤5 mm) assessments beneath these surface accumulation areas are lacking. Using in situ high‐volume filtration, Manta net and MultiNet sampling, combined with micro‐Fourier‐transform‐infrared imaging, we discovered a high abundance (up to 244.3 pieces per cubic meter [n m −3 ]) of small microplastics (SMPs, characteristically 300 μm) concurrently collected in MultiNet samples. Higher‐density polymers (e.g., alkyd resins and polyamide) comprised >65% of the total pump sample count, highlighting a discrepancy between polymer compositions from previous ocean surface‐based surveys, typically dominated by buoyant polymers such as polyethylene and polypropylene. Contrary to previous reports stating LMP preferentially accumulated at density gradients, SMP with presumably slower sinking rates are much less influenced by density gradients, thus resulting in a more even vertical distribution in the water column, and potentially longer residence times. Overall, our findings suggest that SMP is a critical and largely underexplored constituent of the oceanic plastic inventory. Additionally, our data support that weak current systems contribute to the formation of SMP hotspots at depth, implying a higher encounter rate for subsurface particle feeders. Our study unveils the prevalence of plastics in the entire water column, highlighting the urgency for more quantification of the deep‐ocean MP, particularly the smaller size fraction, to better understand ecosystem exposure and to predict MP fate and impacts.

Harmful Algal Blooms in the Alaskan Arctic: An Emerging Threat as the Ocean Warms - Donald Anderson; Evangeline Fachon; Katherine Hubbard; Kathi Lefebvre; Peigen Lin; Robert Pickart; Mindy Richlen; Gay Sheffield; Caroline Van Hemert (Oceanography, 2022)
Harmful algal blooms (HABs) present an emerging threat to human and ecosystem health in the Alaskan Arctic. Two HAB toxins are of concern in the region: saxitoxins (STXs), a family of compounds produced by the dinoflagellate Alexandrium catenella, and domoic acid (DA), produced by multiple species in the diatom genus Pseudo-nitzschia. These potent neurotoxins cause paralytic and amnesic shellfish poisoning, respectively, in humans, and can accumulate in marine organisms through food web transfer, causing illness and mortality among a suite of wildlife species. With pronounced warming in the Arctic, along with enhanced transport of cells from southern waters, there is significant potential for more frequent and larger HABs of both types. STXs and DA have been detected in the tissues of a range of marine organisms in the region, many of which are important food resources for local residents. The unique nature of the Alaskan Arctic, including difficult logistical access, lack of response infrastructure, and reliance of coastal populations on the noncommercial acquisition of marine resources for nutritional, cultural, and economic well-being, poses urgent and significant challenges as this region warms and the potential for impacts from HABs expands.

Observation of summertime upwelling off the eastern and northeastern coasts of Hainan Island, China - Peigen Lin; Jianyu Hu; Quanan Zheng; Zhenyu Sun; Jia Zhu (Ocean Dynamics, 2016)

Evaluation of fungus-induced agilawood from Aquilaria sinensis in China - Jinlong Cui; Chunlan Wang; Shunxing Guo; Lin Yang; Peigen Xiao; Mengliang Wang (Symbiosis, 2013)